EVI1‐mediated Programming of Normal and Malignant Hematopoiesis - Lux, Susanne; Milsom, Michael D. (HemaSphere, 2023)
Ecotropic viral integration site 1 (EVI1), encoded at the MECOM locus, is an oncogenic zinc finger transcription factor with diverse roles in normal and malignant cells, most extensively studied in the context of hematopoiesis. EVI1 interacts with other transcription factors in a context‐dependent manner and regulates transcription and chromatin remodeling, thereby influencing the proliferation, differentiation, and survival of cells. Interestingly, it can act both as a transcriptional activator as well as a transcriptional repressor. EVI1 is expressed, and fulfills important functions, during the development of different tissues, including the nervous system and hematopoiesis, demonstrating a rigid spatial and temporal expression pattern. However, EVI1 is regularly overexpressed in a variety of cancer entities, including epithelial cancers such as ovarian and pancreatic cancer, as well as in hematologic malignancies like myeloid leukemias. Importantly, EVI1 overexpression is generally associated with a very poor clinical outcome and therapy‐resistance. Thus, EVI1 is an interesting candidate to study to improve the prognosis and treatment of high‐risk patients with “EVI1high” hematopoietic malignancies.